BENTUK-BENTUK TEKS DAN KONSEP ASESMEN AS, FOR, DAN OF LEARNING DALAM PEMBELAJARAN - Khairun Nisa; Suhadjah Artika Sari; Salsabila; Rahma Elisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Assessment is an essential component of the learning process that functions to obtain information regarding students’ development and achievement of competencies. This article aims to comprehensively examine the forms of tests used in educational evaluation and the concepts of assessment as learning, assessment for learning, and assessment of learning in instructional practices. This study employed a library research method by analyzing various relevant scientific sources, including journals, books, and academic articles. Data were collected through the identification, review, and synthesis of literature related to educational evaluation and assessment. The findings reveal that commonly used forms of tests include written tests, oral tests, performance tests, as well as diagnostic, formative, and summative tests, each having distinct characteristics and functions according to learning objectives. Furthermore, assessment as learning promotes students’ self-reflection and self-regulation skills, assessment for learning provides feedback to improve the learning process, while assessment of learning is used to measure learning outcomes at the end of instruction. These three assessment approaches complement one another in supporting effective teaching and learning practices. Therefore, a proper understanding and implementation of assessment can assist educators in improving instructional quality and enhancing students’ learning outcomes.